Bacterial community colonization on tire microplastics in typical urban water environments and associated impacting factors. (October 2020) - Wang, Liyuan; Luo, Zhuanxi; Zhen, Zhuo; Yan, Yu; Yan, Changzhou; Ma, Xiaofei; Sun, Lang; Wang, Mei; Zhou, Xinyi; Hu, Anyi
Abstract: Only limited information is available on bacterial communities' dynamics on tire microplastics in urban water environments. This study exploited 16S rDNA high-throughput sequencing to characterize bacterial communities on tire microplastics, using three different tire brands and tire sizes, in two typical urban water environments, including an influent pond of constructed wetland (CW) and its subsequent effluent into a landscape river (LR) during three different periods, namely, 1 month, 3 and 6 months. Results showed that the abundance of bacterial colonization on tire microplastics will increase over time. Proteobacteria, Bacteroidetes were the dominant bacteria at a phylum level, although they exhibited dynamic changes. At a genus level, the identifiable bacteria found in tire microplastics was generally the common bacteria in wastewater discharge, such as Aquabacterium and Denitratisoma . Additionally, alpha diversity showed no significant differences in bacterial communities at the same locations. While beta diversity showed that the bacterial communities on the tire microplastics in the two locations was different. BugBase revealed that tire microplastics could support pathogenic bacteria in urban water environments. PICRUSt (Phylogenetic Investigation of Communities by Reconstruction of Unobserved States) indicated that the abundance of microorganisms associated with metabolism and degradation increased with time. Moreover, the ambient environmental factors were the main influencing factors of bacterial communities on tire microplastics. Herein, the contribution rate of nutrient salts (NO2 -N, NO3 -N, NH4 -N, CODcr) was approximately 63%, and that of environmental physical factors of T and pH was 50%. While physicochemical factors, including particle size, contact angle, element content only had a slight impact. Accordingly, tire microplastics, as an emerging environmental pollutant, can act as carries for bacterial colonization and propagation, particularly harmful microorganisms. Therefore, the obtained findings can provide new insight into potential risks of harmful microorganisms that colonize tire microplastics in urban water environments. Graphical abstract: Image 1 Highlights: Tire microplastics (TMPs) supported pathogenic bacteria in urban water environment. The abundance of bacterial colonization on tire microplastics increased over time. Bacterial communities on TMPs varied in different urban water environment. Urban water factors have significant impacts on bacterial communities on TMPs. Abstract : Our findings can pave the way for understanding bacterial dynamics on tire microplastics in urban water environments.